IMPROVEMENTS IN AI-POWERED REMOTE PATIENT MONITORING FOR HEART PATIENTS AND AI-POWERED INDIVIDUALIZED TREATMENT PLANS (The Research of Medical Science Review, 2025)
Remote Patient Monitoring (RPM) progresses patient-centered care through improved chronic disease monitoring and therapeutic procedures and health results. Digital monitoring technologies let RPM instantly gather essential healthcare data for physicians to make prompt evidence-based decisions thus enhancing home-based patient care and safety. This review article analyzes peer- reviewed studies to examine how Remote Patient Monitoring (RPM) utilizing Artificial Intelligence (AI) transforms the care of heart failure as well as diabetes patients and people suffering from chronic pain. The assessment demonstrates specialized RPM system applications for different health problems while showing how RPM helps patients gain control and knowledge about care while enhancing their medication compliance. Healthcare continuity became possible during systemic disruptions due to the COVID-19 pandemic because remote patient monitoring proved essential for maintaining patient care. The partnership between AI technologies with RPM systems improves their operational abilities by allowing individualized real-time data measurement and processing. This review examines the use of chronic pain management systems alongside investigation of AI technologies for RPM in cardiologic care and diabetic monitoring. The NXTSTIM EcoAI™ serves as an AI-based model which brings substantial prospects to reshape medical interventions through steady tracking and timely responses that lead to better treatment results. Healthcare delivery through advanced AI-driven systems shows RPM can empower improved care quality for patients with different chronic conditions while reducing healthcare system loading of staff. The future usage of AI-integrated RPM will deliver improved and personalized disease management as an instrument for effective treatment decisions. The wider scope of RPM's practical use demonstrates its automated data-based healthcare delivery which both decreases medical system costs and improves patient health while enhancing their daily quality of life.